One Day, One Story: Cultivating a Love of Reading from an Early Age - Sri Utamimah; Bannaga Taha Elzubair Hussen (Al-Qalam Institute, 2024)
This research aims to examine the importance of an interest in reading from an early age in the hope of forming the nation's next generation with high quality and broad insight. A high interest in reading from an early age is an important foundation in forming a child's character and intellect. By reading, children can broaden their horizons and improve their qualities which will be beneficial for their future. One of the methods applied to foster interest in reading in young children is the